2019
DOI: 10.1590/0034-7167-2017-0906
|View full text |Cite
|
Sign up to set email alerts
|

Real and illusory perceptions of patients in induced coma

Abstract: Objective: To identify, in the scientific literature, real and illusory perceptions of adult patients in induced coma. Methods: This is an integrative review of 15 primary studies from the Medline, Web of Science, LILACS, CINAHL and SCOPUS databases. Results: The main memories reported after induced coma were thirst, cold, and pain. In some studies, patients reported they were unable to tell whether they were awake or dreaming, whether it was real or unreal. Satisfactory memories were reported by patients re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
5
0
2
Order By: Relevance
“…Lawrence et al (2020) revealed that thirst sensation as a response to dehydration is principally hindered in unconscious patients. Silva et al (2019) demonstrated that thirst is the most reported memory by critically ill patients when they were comatosed.…”
Section: Discussionmentioning
confidence: 99%
“…Lawrence et al (2020) revealed that thirst sensation as a response to dehydration is principally hindered in unconscious patients. Silva et al (2019) demonstrated that thirst is the most reported memory by critically ill patients when they were comatosed.…”
Section: Discussionmentioning
confidence: 99%
“…No contexto hospitalar, a Unidade de Terapia Intensiva (UTI) caracteriza-se por ser um setor que exige uma atenção complexa, pois atende pacientes que estão clinicamente graves e necessitam de suporte e tratamento crítico, com a utilização de tecnologias avançadas para terapias, diagnósticos e cuidados especializados. 1,2 No âmbito da UTI, a necessidade de sedação e o uso de ventilação mecânica (VM) invasiva é recorrente, sendo muitas vezes imprescindível no tratamento ao paciente crítico.…”
Section: Introductionunclassified
“…Contudo, estudos comprovam que o tratamento intensivo pode desencadear, durante a internação e após a alta, diversas alterações no estado mental, como o delirium, percepções e/ou memórias ilusórias. 2,3,4 Jones et al 5 classificaram as memórias de UTI em três grupos: memória real, memória de sentimento e memória ilusória. As memórias reais são relacionadas ao tratamento (tubo no nariz e boca, extubação, aspiração, etc.)…”
Section: Introductionunclassified
“…According to the memories reported by comatose patients, they could not distinguish whether they were awake or dreaming, whether the reality was actual or imagined. They only reported unpleasant sensations such as pain, cold, or thirst [ 11 ]. At the same time, the hearing could be the last sense to be lost in comatose patients, and some patients said that they had recognized the voice of a family member and remembered a familiar voice pronouncing the patient’s name or some personal words [ 12 - 14 ].…”
Section: Introductionmentioning
confidence: 99%